A hermeneutic analysis of the representation of masculinities in Tsotsi (Hood 2005) and Inxeba (Trengrove 2017) - Lauwrens, Jenni (University of Pretoria, 2025)
Dissertation (MA (Visual Studies))--University of Pretoria, 2024.